Artikel Unraveling the Link Between Fear of Missing Out (FoMO) and Phubbing among University Students - Diah Kurniawati; Egi Prawita (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2024)
The increasing use of social media due to the fear of being left behind and not connected to others is the reason someone engages in phubbing. This study aims to determine the relationship between fear of missing out (FoMO) and phubbing among students at a University in Yogyakarta, Indonesia. This study employs a quantitative method with a correlational design. The research involved 156 students that were selected using a purposive sampling technique. Two measurement were used to collect data, namely the Fear of Missing Out (FoMO) scale and the Phubbing scale. Data analysis was performed using Spearman Rho non-parametric analysis. The results of the data analysis indicated that there is a significant relationship between FoMO and phubbing, where higher levels of FoMO among students are associated with increased phubbing behavior. Conversely, lower levels of FoMO correspond to decreased phubbing. These findings suggest that addressing FoMO could be a key factor in reducing phubbing behavior among university students.